Identification of continuous-time systems : linear and robust parameter estimation - Allamaraju, Subrahmanyam; Prasada Rao, Ganti, 1942- (Boca raton : CRC Press/Taylor & Francis Group, 2020)
'Models of physical systems are originally in continuous-time (CT) since they are based on physical laws which are invariably in CT. To identify these models directly in their native CT form, avoiding intermediate discrete time (DT) model identification, the established method consists of two stages. In the primary stage signals are processed by a general linear dynamic operation- computational or realized through prefilters to preserve the system parameters in their native continuous time form and the literature is rich on this aspect. This book complements the existing literature about identification of continuous-time systems by enhancing the secondary stage by considering models which are linear in unknown parameters thereby rendering estimation linear and robust'--
Includes bibliographical references and index.
Keywords: Automatic control -- Mathematical models; Linear time invariant systems; System identification; Parameter estimation